2013
DOI: 10.1093/bja/aes385
|View full text |Cite
|
Sign up to set email alerts
|

Caudal dexmedetomidine combined with bupivacaine inhibit the response to hernial sac traction in children undergoing inguinal hernia repair

Abstract: The addition of dexmedetomidine to caudal bupivacaine could reduce the response to hernial sac traction, and prolong the duration of postoperative analgesia in children undergoing inguinal hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
64
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 23 publications
6
64
1
Order By: Relevance
“…These results come with agreement with the study done by Xiang et al who studied the effect of addition of dexmedetomidine to ropivacaine in caudal block in children underwent inguinal hernia repair and concluded that the addition of dexmedetomidine to caudal bupivacaine could reduce the response to hernial sac traction, prolong the duration of postoperative analgesia and decrease postoperative analgesic requirements [17].…”
Section: Discussionsupporting
confidence: 91%
“…These results come with agreement with the study done by Xiang et al who studied the effect of addition of dexmedetomidine to ropivacaine in caudal block in children underwent inguinal hernia repair and concluded that the addition of dexmedetomidine to caudal bupivacaine could reduce the response to hernial sac traction, prolong the duration of postoperative analgesia and decrease postoperative analgesic requirements [17].…”
Section: Discussionsupporting
confidence: 91%
“…19) As the sacral region has the largest concentration of α 2 -adrenoceptors than the lumbar or thoracic regions in humans, 20,21) caudally administered DEX combined with local anesthetics could provide effective analgesia. In this current study, although the analgesic duration was shorter than that in other studies that used a higher concentration (0.25%) of bupivacaine 4,[10][11][12][13] or ropivacaine, 17) the analgesic duration Pre-incision, value before surgical incision; Incision, value after surgical incision; 10 min, value 10 min after iincision; End, value at the end of surgery. * p<0.05. was significantly longer in DEX group than in control group.…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, caudal DEX with a low-concentration of local anesthetics induces less adverse effects (motor weakness, delayed micturition of urinary retention) that may affect early discharge from hospital, compared with a higher concentration of local anesthetics. 3,4,10,12,13,23) DEX has anxiolytic, sedative, and hypnotic properties caused by stimulation of the α2-adrenoceptor in the locus coeruleus in brain where it decreases a neuronal activation 9,24) and can reduce the requirement of concomitantly administered hypnotics, analgesics, or anesthetics. 25) Intravenous DEX significantly decreases the sevoflurane requirement 5,26) for anesthesia and EA during recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analgesic effect of dexmedetomidine has been investigated in many (23) found that addition of 5 µg dexmedetomidine to 10 mg bupivacaine intrathecally in patients before major abdominal cancer surgery improved the duration and quality of postoperative analgesia. In a previous study, Xiang et al (24) added dexmedetomidine to bupivacaine in 60 children aged 1-6 years. Thirty children received 1 mL/kg volume of 0.25% bupivacaine plus 1 μg/kg dexmedetomidine caudally.…”
Section: Discussionmentioning
confidence: 99%